Enzyme Kinetics in Drug Metabolism Fundamentals and Applications - Nagar, Swati; Argikar, Upendra A.; Tweedie, Donald J.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2014)
Drug metabolism and transport are very important facets within the discipline of pharmaceutical sciences, with  enzyme kinetic concepts utilized regularly in characterizing and modeling the disposition and elimination of drugs. Enzyme Kinetics in Drug Metabolism: Fundamentals and Applications focuses on very practical aspects of applying kinetic principles to drug metabolizing enzymes and transporters. Divided into five convenient sections, topics include the fundamental principles of enzyme kinetics, the kinetics of oxidative and conjugative drug metabolizing enzymes and drug transporters, modeling approaches for both drug metabolizing enzymes and transporters including novel systems biology approaches, understanding of variability both experimental and interindividual (pharmacogenomic), and case studies that provide real life examples of applying these principles. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics especially suitable for the novice, in some cases step-by-step, readily reproducible protocols, and insights to help with troubleshooting and avoiding known pitfalls with extensive cross referencing to assist in learning.   Authoritative and easily accessible, Enzyme Kinetics in Drug Metabolism: Fundamentals and Applications serves as a very practical teaching tool for novice, non-mathematically trained scientists interested in these fundamental concepts and as an aid for their supervisors in teaching these principles.   .
Enzyme Kinetics in Drug Metabolism – Fundamentals and Applications -- Fundaments of Enzyme Kinetics -- Different Enzyme Kinetic Models -- Reversible Mechanisms of Enzyme Inhibitors and Resulting Clinical Significance -- Irreversible Enzyme Inhibition Kinetics and Drug-Drug Interactions -- Multi-Enzyme Kinetics and Sequential Metabolism -- Consideration of the Unbound Drug Concentration in Enzyme Kinetics -- Enzyme Kinetics of Oxidative Metabolism – Cytochromes P450 -- Enzyme Kinetics, Pharmacokinetics, Inhibition, and Regioselectivity of Aldehyde Oxidase -- Enzyme Kinetics of Conjugative Enzymes – PAPS -- Enzyme Kinetics of Uridine Diphosphate Glucuronosyltransferases (UGTs) -- Principles and Experimental Considerations for in vitro Transporter Interaction Assays -- Rationalising Under-Prediction of Drug Clearance from Enzyme and Transporter Kinetic Data – from in vitro Tools to Mechanistic Modeling -- The Structural Model for the Mass Action Kinetic Analysis of P-gp Mediated Transport Through Confluent Cell Monolayers -- Systems Biology Approaches to Enzyme Kinetics: Analyzing Network Models of Drug Metabolism -- Variability in Human in vitro Enzyme Kinetics -- Sources of Interindividual Variability -- Case Study 1. Practical Considerations with Experimental Design and Interpretation -- Case Study 2. Practical Analytical Considerations for Conducting in vitro Enzyme Kinetic Studies -- Case Study 3. Application of Basic Enzyme Kinetics to Metabolism Studies – Real Life Examples -- Case Study 4. Predicting the Drug Interaction Potential for Inhibition of CYP2C8 by Montelukast -- Case Study 5. Deconvoluting Hyperbilirubinemia: Differentiating Between Hepatotoxicity and Reversible Inhibition of UGT1A, MRP2 or OATP1B1 in Drug Development -- Case Study 6. Drug Transporters: in vitro Solutions for Translatable Outcomes -- Case Study 7. Compiled Aha Moments in Enzyme Kinetics: Authors’ Experiences.
Keywords: Pharmacology; Enzymology; Pharmacology/Toxicology.; Enzymology